Determination of compensation ratios of al-implanted 4H-SIC by tcad modelling of TLM measurements - Kocher, Matthias; Yao, B.; Weiße, Julietta; Rommel, Mathias; Xu, Z. W.; Erlbacher, Tobias; Bauer, Anton (Materials Science Forum, 2019)
The prediction of the compensation induced hole concentration reduction in implanted Al regions is a key parameter in developing high power SiC devices. Hall effect measurements are commonly used to determine the compensation ratio of Al implanted regions. Due to the fact that this measurement method is rather complex, an approximate method was developed by using transfer length method structure measurements in combination with a TCAD simulation model. The determined compensation ratios from this work’s simulation and from Hall effect measurements from literature show consistent compensation ratios. Based on this data a fit function was derived which allows for estimating the compensation ratio for a wide Al concentration range.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Al implantation; Compensation; Simulation; TCAD